Mecanismos de sinalização endotelial envolvidos na atividade cardiovascular do α-terpineol - Ribeiro, Thaís Pôrto (2012)
The essential oils are volatile organic constituents found in aromatic plants, which present several monoterpenes, such a-terpineol. Studies have demonstrated some biologic activities such as hypotensive and vasorelaxant (Guedes et al., 2004). In the present work the cardiovascular effects of a-terpineol was investigated and the pharmacodynamics of this effect was characterized. Wistar Kyoto and spontaneously hypertensive rats (SHR) were anaesthetized and polyethylene catheters were inserted into the low abdominal aorta and inferior vena cava for blood pressure measurements and administration of drugs. Isolated superior mesenteric rings (1-2 mm) were suspended by cotton threads for isometric tension recordings in Tyrode s solution (37°C, gassed with 95% O2 and 5% CO2), under 0.75g resting tension were measured by using pressure transducers, coupled to a computer set and CVMS software Miobath-4, WPI, Sarasota, EUA. In addition, the bioavailability of NO and eNOS, AKT and AMPK activity were quantified when exposing cells to α-terpineol in the cultured endothelial cells. In both SHR and normotensive rats, i.v. bolus injections of α-terpineol (1 20 mg/kg) decreased mean arterial pressure (MAP) in a dose-related manner, WKY (-103, -399, -5211, -6212 mmHg, n=10) and SHR (-375, -577, -715, -844 mmHg, n=9) associated with tachycardia. However, hypotensive and tachycardic responses were significantly attenuated after L-NAME (20 mg/kg, i.v.). The -terpineol demonstrated improves the baroreflex sensitivity. In intact isolated rat mesenteric rings -terpineol (10-12 10-5M) induced concentration-dependent relaxation of the contractions induced by phylephrine (10M) WKY Emax= 60  4 or SHR Emax= 53.7 ± 3, p<0.05, n=9). After endothelium removal the vasorelaxant elicited by -terpineol was significantly attenuated WKY [Emax= 20.5  1*] and SHR [Emax= 16.1 ± 3*, p<0.05, n=8]. Similar results were obtained in the presence of L-NAME 100M, a competitive antagonist of NOS, hydroxocobalamin 30 μM, a NO scavenger or ODQ 10μM, a selective inhibitor of soluble guanylyl cyclase. In addition, in endothelial cells, a-terpineol increased eNOS activation and NO levels by phosphorylation of PI3K/ AKT and AMPK pathway. However, atropine (1ηM) or indometacin (10 μM) had no effect on the a-terpineol -induced vasorelaxation. Furthermore, vasorelaxation was significantly attenuated in the presence of 20 mM KCl a modulator K+ efflux or several blocking of potassium channels: 1mM 4-aminopirimidine, 10 M glibenclamide, 1 mM tetraethylammonium and carybdotoxin plus apamin (0.2uM). In conclusion, the present study demonstrated that a-terpineol induced hypotensive effect, probably due to a decrease of peripheral vascular resistances, which seems to be mediated by endothelium derived relaxant factors, at least NO induced. These results suggest that vasorelaxant response, almost completely mediated by the endothelium, likely via NO release and activation eNOS by PI3K and AMPK with consequently activation of NO-cGMP pathway and potassium channels activation at least, KCa, KV, and KATP are involved in the vasorelaxant effect induced by a-terpineol.